Comprehensive Study on Chain-End Transformation of Polymer–Iodides with Amines for Synthesizing Various Chain-End Functionalized Polymers - Chen, Chen (2017)
Chain-end functionalized polymers (polymer–NHR) were successfully synthesized through the reaction of a polymer–iodide (polymer–I) with a primary amine (NH2R), where the R moiety contains a functional group. This reaction was comprehensively studied for three different polymers, i.e., poly(butyl acrylate), polystyrene, and poly(methyl methacrylate), and six different functional amines with phenyl, alkyl, triethoxysilyl, SH, OH, and NH2 functionalities, and the detailed reaction mechanisms were probed by using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI–TOF–MS). This chain-end transformation reaction is easy to perform, amenable to various polymers and functional amines, and also quantitative and selective in many cases. This synthetic technique may serve as a useful platform method for synthesizing various chain-end functionalized polymers.